UPAYA MENINGKATKAN KINESTETIC INTELRGENCY DENGAN PERMAINAN LOMPAT TALI PADA SISWA KELAS 3 MIS AL-IHKLAS SIDODADI RAMUNIA - Lestari, Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstrak This research aims to find out: 1) Is there an increase in children's kinesthetic intelligence before using the method of playing jump rope at school MIS AL-IKHLAS SIDODADI RAMUNIA, 2) How is the method of playing jumping rope at school MIS AL-IKHLAS SIDODADI RAMUNIA implemented, 3) Is there an increase kinesthetic intelligence after using the jumping rope playing method at the MIS AL-IKHLAS SIDODADI RAMUNIA school, 4) How do students respond when using the jumping rope playing method in developing kinesthetic intelligence at the MIS AL-IKHLAS SIDODADI RAMUNIA school. This type of research is Classroom Action Research (PTK) with research subjects of children aged 9-10 years consisting of 29 children. The object of this research is to increase children's creative movement abilities. The data collection technique is through observation in the form of a checklist and documentation in the form of photos. Data analysis techniques use qualitative and quantitative analysis. The research results obtained during the research were as follows: 1) Before using the Jump Rope Game at the MIS AL-IKHLAS SIDODADI RAMUNIA school, in the pre-cycle 13 children received the BB criteria, 9 children received the MB criteria and 7 children received the BSH criteria. There are no children yet who have reached the score of 16, so the child's completion is still 0%. 2) Carrying out the jump rope game in cycle I, the child must jump over the rope without being hit by the rope that has been agreed upon before the game starts, in cycle II the child must reach the number of rope jumps that have been agreed upon by the researcher. 3) There was an increase after using the jumping rope playing method with a value of 10 points from an average value of 6, increasing to an average value of 16, this shows that the research in cycle I and cycle II has achieved an increase in classical success. Keywords: Traditional Games, Jump Rope, Kinesthetic Intelligence, Criteria